Association Between Antiretroviral Therapy Initiation Timing and Clinical Outcomes in HIV/AIDS Patients with Toxoplasmic Encephalitis at Haji Adam Malik Hospital, Medan - Bangun, Esmeralda Joseva (Jurnal sosial dan sains, 2025)
Toxoplasmic encephalitis (TE) is one of the most prevalent opportunistic infections affecting HIV/AIDS patients, especially those with depleted CD4 levels. The decision regarding the timing of antiretroviral therapy (ART) initiation in the context of opportunistic infections such as TE is still debated. Although early initiation of ART enhances immune recovery and reduces viral replication, it also poses a higher risk for the development of immune reconstitution inflammatory syndrome (IRIS). Methods: This study assessed clinical outcomes using the Glasgow Outcome Scale (GOS) as a measure of neurological status following treatment. Data were collected from HIV patients with toxoplasmic encephalitis (TE) who received toxoplasmosis therapy. A comparative analysis of clinical outcomes was conducted between early and delayed ART initiation groups. Results: There was an association observed between the timing of antiretroviral therapy (ART) initiation and clinical outcomes in patients with toxoplasmic encephalitis (p=0.002). The findings indicate that earlier initiation of ART is associated with better clinical outcomes, as measured by the Glasgow Outcome Scale (GOS), in patients with toxoplasmic encephalitis.